Project-Based Learning E-Modules Improve Science Literacy Skills and Character on Minangkabau Cultural Themes - Eka Sriwahyuni; Delfi Eliza (Jurnal Pendidikan Indonesia, 2024)
The current problem is the need for more learning media to stimulate children's scientific literacy. Based on this, this research aims to develop a project-based learning E-module. The subjects of this research were one material expert, one media expert, and one language expert. The test subjects for this research were four teachers (practicality test) and 15 kindergarten group B children. Observation, interviews, questionnaires, and documentation are used to collect data. The instrument used to collect data was a questionnaire sheet. The techniques used to analyze data are qualitative descriptive analysis and quantitative analysis. The results of the research are: The results of the research obtained scores from material experts (85%) in the valid category, scores from media experts (67%) in the valid category, and scores from language experts (96%) in the very valid category. The results of the teacher practicality test obtained a score of (90%) in the very practical category, the results of assessing children's character abilities (92%) in the very practical category, the results of evaluating scientific literacy abilities (90%) in the very practical category. It was concluded that project-based learning modules with Minangkabau cultural themes can develop students' scientific literacy skills and character in kindergarten.